Involvement of State Officials As Cast of Characters in Folk Theater Ketoprak RRI Yogyakarta - Joe Harrianto Setiawan; Santi Indra Astuti; Rawi Diwangkara; Daniari Setiawati (Gondang: Jurnal Seni dan Budaya, 2024)
Ketoprak is a traditional Javanese performing art that incorporates elements of karawitan, dance, comedy, song, acting, and artistic arrangements. Traditional art is divided into two types, such as folk art and classical art, or palace art. Ketoprak is a folk art that has its origins among the people who live outside the palace. As a folk art, ketoprak is also used to communicate to the authorities issues that the people are concerned about. Criticizing through the performing arts is a powerful way to express criticism without taking offense. Ketoprak is usually performed by a group of artists on stage. However, in recent years, ketoprak performances have been performed not only by community performer groups but also by state officials taking the cast of characters on stage. The involvement of state officials at all levels, from regional to ministerial, as well as guest stars and main characters. Including those carried out under the RRI Yogyakarta ketoprak program. The descriptive qualitative research method was used to figure out how the implementation of the ketoprak program at RRI can preserve ketoprak's dignity as a folk theater, despite the fact that it is represented by state officials, by conducting interviews with program producers and respected ketoprak performers from Yogyakarta. The study's findings show that in its development, ketoprak was divided into two forms, conventional ketoprak which was standard with rules or pakem that were still preserved by RRI Yogyakarta and ketoprak garapan which is open to be interpreted in various ways and is free to be casted by anyone, including officials who are performed in the live version of the RRI Ketoprak Program.